Effect of Relative Density Variation on The Effectiveness of Fly Ash in Stabilization of Sandy Soils for Liquefaction Mitigation - Yunan Yakuta Wangsawitana; Muhammad Fauzan; Heriansyah Putra; Erizal; Minson Simatupang (Journal of the Civil Engineering Forum, 2026)
Indonesia is highly vulnerable to earthquakes that can trigger soil liquefaction, particularly in coastal regions where saturated sandy soils with low relative densities are prevalent. This study investigated the influence of varying Class C fly ash contents (5%, 10%, and 15%), relative densities (50%, 70%, and 90%), and curing periods (7 and 14 days) on the unconfined compressive strength of fully saturated sandy soils as a liquefaction mitigation approach. The methodology included physical soil characterization, sample preparation with specific fly ash and relative density variations, and unconfined compressive strength testing after the curing period. The results demonstrated that increasing the fly ash content, relative density, and curing time significantly enhanced the strength of the samples. The highest strength occurred at 15% fly ash and 90% relative density, with 426.22 kPa (7 days) and 438.57 kPa (14 days). The most notable improvement occurred with an increase in fly ash content from 5% to 10% and relative density from 50% to 70%. Fly ash was more effective at enhancing the strength of sandy soil by promoting interparticle cementation, whereas excessive compaction tended to disrupt the soil structure and generate fine particles that reduced cohesion, as evidenced by the UCS test results and SEM observations. The most significant strength gain between 7 and 14 days was observed at 50% relative density and 5% fly ash, with a twofold increase. The combination of 10% fly ash and 70% relative density was optimal for field implementation, as it yielded strength values exceeding the liquefaction resistance thresholds, while maintaining practical compaction levels and material efficiency. A comparative cost assessment considering materials, labor, equipment, and construction time is recommended to evaluate the practical feasibility of fly ash stabilization relative to alternative ground improvement methods for Indonesian projects.